2011
DOI: 10.1118/1.3533900
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance of volumetric modulated arc therapy: Evaluation and comparison of different dosimetric systems

Abstract: The presented results for VMAT plans QA assess the reliability of the delivered doses for both TPSs. The slightly lower pass-rate obtained for one of the considered TPS can be attributed to a higher level of complexity of the optimized plans. The results by different dosimetric techniques are coherent, apart from a few measurements by gafchromic films. The detector sensitivity to delivery errors, being strongly plan dependent, is not easy to evaluate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 41 publications
1
57
0
Order By: Relevance
“…In either case, it is important to know how sensitive a particular dosimetric technique, paired to a particular linac, is to MLC leaf position errors as well as other rotational or translational errors that could compromise quality. Masi et al 52 reported recently that DELTA4 and MAPCHECK dosimetric systems for VMAT QA varied in sensitivity for some plans, where a 3…”
Section: Discussionmentioning
confidence: 99%
“…In either case, it is important to know how sensitive a particular dosimetric technique, paired to a particular linac, is to MLC leaf position errors as well as other rotational or translational errors that could compromise quality. Masi et al 52 reported recently that DELTA4 and MAPCHECK dosimetric systems for VMAT QA varied in sensitivity for some plans, where a 3…”
Section: Discussionmentioning
confidence: 99%
“…Other assemblies furnish dosimetric data corresponding to the gantry position using phantoms characterized by opportune geometries or rotation capability, as SunNuclear ArcCHECK ® , Scandidos Delta4 ® phantom, the IBA Compass, and PTW Octavius ® ‐4D. Many studies report a comparison of these devices, assessing their different responses as well as their ability in detecting intentional errors,4, 5, 6 or they were used in the validation process of novel QA strategies 7, 8. The present study is focused on PTW Octavius ® ‐4D.…”
Section: Introductionmentioning
confidence: 99%
“…Korreman et al (10) demonstrated the delivered dose distribution measured with a diode array to be in agreement with the TPS for over 96% of points in the gamma maps calculated at 3% and 3 mm. Masi et al (11) developed a protocol for dosimetric verification of VMAT, which compares TPS dose distributions to the one measured with film (radiographic and GAFCHROMIC), a diode or an ionization chamber array. Although the authors provided extensive analysis using gamma maps and investigated delivery faults, including linear shift of the leafs and the gantry offset, they did not address the concept of the DLG, which is a part of QA of VMAT.…”
Section: Introductionmentioning
confidence: 99%